PSYCHOLOGICAL FACTORS FOR SUCCESSFUL EVALUATION OF SCIENTIFIC INFORMATION - Islomov Nurtoy Namoz ugli (American Journals, 2023)
The article analyzes the role of cognitive processes in the process of assimilation of educational information, psychological factors for the successful assimilation of scientific information, the importance of mental processes formed in students, the inclusion of mental processes in accordance with the indicated stages of information assimilation.
Keywords: Cognitive processes, understanding, perception, memory, thinking, goal, education, activity, educational activity, professional activity, individuality.